Academic Publication of Neurodegenerative Diseases From a Bibliographic Perspective: A Comparative Scientometric Analysis - Shi, Jian; Liao, Zhenxin; Yang, Mengling; Kuang, Xuyuan; Wei, Wei (Frontiers in Aging Neuroscience, 2021)
BACKGROUND: For measuring the impact in clinical and scientific research, the citation count of the articles is used in the bibliometric analysis, though there is no comprehensive summary of neurodegenerative diseases research. This article intends to provide the neuroscientists and investigators with a practical reference guide to appraise the most important and influential articles written on this subject through a macroscopic view of the research activities on neurodegenerative diseases. MATERIAL AND METHOD: The Clarivate Analytics Web of Science were searched on July 2020. To ensure the breadth of the search scope, the search terms were confirmed as "multiple sclerosis" (MS) or "amyotrophic lateral sclerosis" (ALS) or "Parkinson's" or "Alzheimer's" or "Huntington's" or "neurodegenerative". After excluding completely unrelated articles, top-cited articles were collected and evaluated from special characteristics. The data analysis was performed using SPSS 18.0.The articles were characterized by citation number, publication year, topic, study type, authorship, journal, country, and institute of responding author and foundation. RESULTS: The query identified 593,050 articles. Forty-five percent of the top-cited articles were published during 2000-2009, followed by 30 articles from 1990-1999. Diagnostic and pathology were the main research categories（n=62）. Alzheimer’s disease (AD) was the main study topic（n=43）. Meanwhile, the US confirmed the tremendous impact on the research field. 69 of 100 articles were studied in the US. There were only 22 papers can be divided by evidence level. No article was categorized as level 1 evidence. In the journal list with multiple articles, 7 of 15 were general journals. The 58 authors, who contributed to more than 1 paper, have been identified by VOS viewer and the clusters of authors reveal the evolution of research focus in neurodegenerative diseases. CONCLUSIONS: This study analyzed the bibliometric characteristics and connections of are top-cited articles in the field of neurodegenerative diseases. There were their main outcomes. First, the pathology and diagnostic researches took a big role in 100 top-cited articles while the therapy articles are relatively less. Second, the US confirmed the tremendous impact on the field of neurodegenerative diseases. Third, researchers also submitted their researches to general journals, not just focused on specialty journals.